Managing up : forge strong ties, set clear expectations, promote your ideas. (Boston, Massachusetts : Harvard Business Review Press, 2014)
Succinctly delivers information on managing an employee-employer relationship, including understanding your manager's priorities and pressures, managing expectations and egos, and earning trust and respect.
What is managing up? -- Knowing your manager and yourself -- Managing expectations -- Communicating with your manager -- Negotiating with your manager.
Includes bibliographical references and index.
Keywords: Managing your boss; Management; Management; Managing your boss